2001
DOI: 10.1590/s0066-782x2001000900004
|View full text |Cite
|
Sign up to set email alerts
|

Laser assisted extraction of pacemaker and implantable defibrillator leads

Abstract: Objective -To analyze the results of laser-assisted extraction of permanent pacemaker and defibrillator leads. Methods -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Calcified adhesions have also been implicated in unsuccessful LLE in the series of Costa et al, who reported a LLE failure rate of 3.6% (two of 56 leads attempted) in adults without CHD. Calcium was observed along the trajectory of these two leads, leading the authors to suggest that the LLE failures were related to calcified adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Calcified adhesions have also been implicated in unsuccessful LLE in the series of Costa et al, who reported a LLE failure rate of 3.6% (two of 56 leads attempted) in adults without CHD. Calcium was observed along the trajectory of these two leads, leading the authors to suggest that the LLE failures were related to calcified adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…In both conventional and laser extraction methods, advancement of the sheath may fail due to the “snowplough” effect at the advancing sheath tip if sufficient spacing is not allowed between the lead and the sheath 3 . Thus, the ability to gauge the appropriate size of sheath is common to both techniques 12 . It remains to be seen whether operators that do not have experience with conventional extraction methods demonstrate a learning curve with laser lead extraction.…”
Section: Discussionmentioning
confidence: 99%
“…3 Thus, the ability to gauge the appropriate size of sheath is common to both techniques. 12 It remains to be seen whether operators that do not have experience with conventional extraction methods demonstrate a learning curve with laser lead extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the issue of NTL extraction 11–14 , 19–22 . Costa et al 15 recently described their experience using LASER for extraction of 56 relatively long‐standing pacemaker and NTLs (mean implantation time 7.5 years), 9 of which were ICD leads. Clinical success was obtained in 96% of cases and complete lead extraction was possible in 82%.…”
Section: Discussionmentioning
confidence: 99%
“…The use of LASER sheaths produces a controlled ablation of the fibrous tissue attachments to the vascular structures, a more predictable time course and quicker lead removal, and fewer partially removed leads. Recently published experience with LASER sheath‐assisted extraction of pacemaker leads and NTLs 10–15 documented safety and efficacy of such devices. When there is excessive fibrosis or calcification, particularly between the clavicle and the first rib, use of specially designed metal sheaths are used to cut through the scar tissue.…”
Section: Methodsmentioning
confidence: 99%